2016
DOI: 10.1186/s13059-016-1109-7
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the origin of disseminated tumor cells in breast cancer using single-cell sequencing

Abstract: BackgroundSingle-cell micro-metastases of solid tumors often occur in the bone marrow. These disseminated tumor cells (DTCs) may resist therapy and lay dormant or progress to cause overt bone and visceral metastases. The molecular nature of DTCs remains elusive, as well as when and from where in the tumor they originate. Here, we apply single-cell sequencing to identify and trace the origin of DTCs in breast cancer.ResultsWe sequence the genomes of 63 single cells isolated from six non-metastatic breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 50 publications
2
40
1
Order By: Relevance
“…In particular, the vast majority of driver mutations found in the primary cancer would also be present in the relapsing clone. Our observation of late dissemination is consistent with the findings of a recent study that combined bulk sequencing of primary tumors with single-cell sequencing of bone marrow-derived disseminated tumor cells, the presumed precursor of clinically overt metastatic disease ( Demeulemeester et al., 2016 ). Although the genome of a metastatic clone may be similar to the primary tumor at first diagnosis, by the time it has expanded to be clinically detectable, extensive further genomic changes have occurred.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, the vast majority of driver mutations found in the primary cancer would also be present in the relapsing clone. Our observation of late dissemination is consistent with the findings of a recent study that combined bulk sequencing of primary tumors with single-cell sequencing of bone marrow-derived disseminated tumor cells, the presumed precursor of clinically overt metastatic disease ( Demeulemeester et al., 2016 ). Although the genome of a metastatic clone may be similar to the primary tumor at first diagnosis, by the time it has expanded to be clinically detectable, extensive further genomic changes have occurred.…”
Section: Discussionsupporting
confidence: 91%
“…All three different methods employ the detection of cytokeratins as marker of epithelial cells. However, it should be mentioned here that the immunocytochemical staining of bone marrow aspirates for a broad spectrum of cytokeratins in patients with breast cancer, showed that the true positive rate for the detection of disseminated tumor cells was 52.6±11.5% [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, single-cell genotyping has become a very popular method, allowing determination of cancer "phylogenesis" and evolution. Demeulemeester et al have constructed cancer "phylogenetic" trees using singlecell sequencing (52).…”
Section: Morphology and Biological Features Morphological Evaluationmentioning
confidence: 99%